Essential Oils of Two Varieties of Gundelia tournefortii L. (Asteraceae) from Turkey - Bagci, Eyup; Hayta, Sukru; Kilic, Omer; Kocak, Alpaslan (Asian Journal of Chemistry, 2010)
The chemical composition of the essential oils of dried aerial parts of two varieties of Gundelia tournefortii L. (var. tournefortii and var. armata Freyn and Sint.) (Asteraceae) from Turkey were analyzed by GC and GC-MS 75 components in both of the plants were identified representing 87.7 and 78.9% of the oils, respectively. The main compound of Gundelia tournefortii var. tournefortii is thymol (24.5 %) and for Gundelia tournefortii var. armata is Germacrene D (21.6 %). The results were discussed in terms of natural products, renewable resources and chemotaxonomy.
Keywords: Gundelia tournefortii var. tournefortii; Gundelia tournefortii var. armata; Asteraceae; GC-MS; Essential oil